Pengaruh Campuran Feses Sapi Potong dan Feses Kuda Pada Proses Pengomposan Terhadap Kualitas Kompos - Hidayati, Yuli Astuti; Marlina, Eulis Tanti; Benito AK, Tb; Harlia, Ellin (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
ThisÂ studyÂ aimsÂ toÂ determineÂ compostÂ qualityÂ (contentÂ ofÂ Â N,Â P2O5, K2O)Â generatedÂ fromÂ various mixturesÂ ofÂ beefÂ cattleÂ fecesÂ andÂ theÂ fecesÂ ofÂ horses.Â The methodÂ Â Â usedÂ Â Â inÂ thisÂ studyÂ isÂ theÂ experimental method in the laboratory using a completely randomized design with 3 treatments, ie P1 = C / N ratio of 25, P2Â =Â CÂ / NÂ ratioÂ ofÂ 30Â andÂ P3Â =Â CÂ / NÂ ratioÂ ofÂ 35Â andÂ replicationsÂ 6Â times.Â ToÂ determineÂ theÂ effectÂ of treatments, data were analyzed with ANOVA and Duncan test. The results showed that the mixture of feces of beefÂ cattle and horseÂ feces with various CÂ / NÂ ratio did notÂ significantly affectÂ the quality ofÂ compost. N contentÂ inÂ compostÂ produced =Â 0.7867Â toÂ 0.8000%, P2O5Â content =Â 0.5883Â toÂ 0.6000%, K2O =Â 0.5733Â to 0.5883%